Pemberian Kompres Dingin Untuk Mengurangi Nyeri Disminore Pada Siswi SMP - reni trevia; Daeng Ramadhan; ikrimni (Jurnal Amanah Kesehatan, 2024)
ABSTRACT In Indonesia, 107,673 people (64.25%), consisting of 59,671 people (54.89%) experienced primary dysmenorrhoea and 9,496 people (9.36%) experienced secondary dysmenorrhoea. The aim of the research was to determine the effect of cold compresses on pain in Baiturrahmah Middle School students in Padang. This type of research uses quantitative, namely pre-experimental with a one group pretest posttest design. The research was conducted at Baiturrahmah Padang Middle School from March-August 2023. The sampling technique was purposive sampling. The sample size is 9 respondents. The results of the bivariate test using the T-test showed p = 0.001<0.05. From the results above it can be concluded that there was a significant change in the scale of dysmenorrhoea in Baiturrahmah Padang Middle School students after being given a cold compress. Key words: dysmenorrhea; cold compress